Tata Laksana Sindrom Koroner Akut dengan Elevasi Segmen ST Sadapan aVR di Rumah Sakit dengan Fasilitas Terbatas: Laporan Kasus - David Kristianus; Yuliana Rias Mayasari; Leona Friyanti Ngadiah (Cermin Dunia Kedokteran, 2024)
Analysis of aVR leads on electrocardiography (ECG) is often given less attention, when in fact ST-segment elevation in aVR leads and diffuse ST-segment depression in other leads indicates circumferential subendocardial ischemia, which can be caused by left main coronary artery occlusion (LMCA) or three-vessel coronary artery disease (3VD) and is associated with a poor prognosis. An 83-year-old male came to the emergency room with chest pain for 18 hours. The ECG showed ST-segment elevation in the aVR with diffuse ST-segment depression in the anteroinferolateral leads. He was diagnosed with acute coronary syndrome (ACS), suspected occlusion of the left main coronary artery (LMCA), and a differential diagnosis of three-vessel coronary artery disease (3VD). Examination of cardiac markers and cardiac catheterization facilities were not available. A loading dose of aspirin and clopidogrel was given. During in-hospital treatment, ECG evaluation showed improvement of aVR ST-segment elevation. Early recognition of ACS with aVR ST-segment elevation and prompt early management are important.